Factors Influencing Pap Screening Use Among African Immigrant Women. (September 2017) - Adegboyega, Adebola; Hatcher, Jennifer
Purpose: Papanicolau (Pap) screenings disparities exist for immigrant women in the United States. This study sought to have an understanding of factors influencing Pap screening among sub-Saharan African immigrant women.Method: This is a qualitative descriptive study. Women were recruited from the community and by word of mouth following institutional review board approval. Data were gathered through in-depth focus group and demographic questionnaires. Interview sessions were digitally recorded and transcribed verbatim. Transcripts were analyzed for themes.Findings: Twenty-two women aged 24 to 65 years were interviewed. Barriers to screening included low knowledge of screening, cost, cultural beliefs, fear and communication issues. Motivators to improve Pap use include provider's recommendations, enlightenment, and family support.Discussion: Interventions addressing the barriers peculiar to this population may alleviate these barriers and improve Pap screening use in this population. Providers have the opportunity to influence screening attitudes of African-born women by providing awareness and patient-targeted interventions.